2014
DOI: 10.1186/s13058-014-0491-x
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor activation downregulates GATA3 by transcriptional repression and increased protein turnover promoting breast tumor growth

Abstract: IntroductionThe transcription factor GATA3 is involved in mammary gland development and is crucial for the maintenance of the differentiated status of luminal epithelial cells. The role of GATA3 in breast cancer as a tumor suppressor has been established, although insights into the mechanism of GATA3 expression loss are still required.MethodsChromatin immunoprecipitation assays were conducted to study progestin modulation of recruitment of transcription factors to GATA3 promoter. We performed western blot and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…76 To study the expression of urokinasetype plasminogen activator, conditioned media were concentrated using Centricon spin columns (Amino, Beverly, MA, USA). Zymographic analysis was performed as described.…”
Section: Cell Lines and Treatmentsmentioning
confidence: 99%
“…76 To study the expression of urokinasetype plasminogen activator, conditioned media were concentrated using Centricon spin columns (Amino, Beverly, MA, USA). Zymographic analysis was performed as described.…”
Section: Cell Lines and Treatmentsmentioning
confidence: 99%
“…Krüppel-like factor 5 (KLF5) is another transcription factor upregulated by progesterone in breast cancer cells [61, 100]; knockdown of KLF5 impaired progesterone-mediated induction of CK5, whereas overexpression of KLF5 in the absence of progesterone was able to increase CK5 expression [109]. Progestins also downregulate the transcription factor (and Notch target gene) GATA3, which is associated with maintaining the luminal epithelial phenotype [110]. Using a high content screen, we found that several retinoic acid (RA) compounds were potent inhibitors of progesterone induction of CK5 in T47D breast cancer cells [59].…”
Section: Downstream Signaling Pathways and Transcription Factors Thatmentioning
confidence: 99%
“…miR-29a inhibition also potentiated the progestin-mediated increases in both the CD44+ and CK5+ breast cancer cell populations [53]. Progesterone also downregulates GATA3 in breast cancer cells [110], which has been shown to increase miR-29b expression to promote a differentiated phenotype and suppress metastasis [118]; the progestin-induced down-regulation of miR-29b could therefore increase the breast CSC population partially through lowering GATA3.…”
Section: Steroid Hormone-regulated Micrornas and Breast Cscsmentioning
confidence: 99%
“…The role of GATA3 in breast cancer as a tumor suppressor has been established. Interestingly, the GATA3 down-regulation is required for the progestin-induced upregulation of cyclin A2(CCNA2) and for progestininduced in vivo and in vitro breast cancer cell growth [25]. Thompsons et al presented low expression of LRIG1 is a prognostic factor for breast cancer patients [26].…”
Section: Discussionmentioning
confidence: 99%